Basal‐like and classical cells coexist in pancreatic cancer revealed by single‐cell analysis on biopsy‐derived pancreatic cancer organoids from the classical subtype. Issue 9 (20th July 2020) - Juiz, Natalia; Elkaoutari, Abdessamad; Bigonnet, Martin; Gayet, Odile; Roques, Julie; Nicolle, Rémy; Iovanna, Juan; Dusetti, Nelson
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is composed of stromal, immune, and cancerous epithelial cells. Transcriptomic analysis of the epithelial compartment allows classification into different phenotypic subtypes as classical and basal‐like. However, little is known about the intra‐tumor heterogeneity particularly in the epithelial compartment. Growing evidences suggest that this phenotypic segregation is not so precise and different cancerous cell types may coexist in a single tumor. To test this hypothesis, we performed single‐cell transcriptomic analyses using combinational barcoding exclusively on epithelial cells from six different classical PDAC patients obtained by Endoscopic Ultrasound (EUS) with Fine Needle Aspiration (FNA). To purify the epithelial compartment, PDAC were grown as biopsy‐derived pancreatic cancer organoids. Single‐cell transcriptomic analysis allowed the identification of four main cell clusters present in different proportions in all tumors. Remarkably, although all these tumors were classified as classical, one cluster present in all corresponded to a basal‐like phenotype. These results reveal an unanticipated high heterogeneity of pancreatic cancers and demonstrate that basal‐like cells, which have a highly aggressive phenotype, are more widespread than expected.